2020
DOI: 10.33448/rsd-v9i8.4894
|View full text |Cite
|
Sign up to set email alerts
|

Efficient management of the application of paclobutrazol for the production and quality of 'Tommy Atkins' mango

Abstract: The application of paclobutrazol (PBZ) by irrigation system to induce the flowering of mango may be an economically and environmentally more efficient practice. The objective of this work is to determine the most efficient dose of PBZ to be applied by irrigation system to manage the production and quality of fruits of the mango cultivar ‘Tommy Atkins’ in the middle region of the São Francisco Valley. The experimental design was randomized blocks with five paclobutrazol doses applied by irrigation system (0.5, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Total soluble solids content in 'Tommy Atkins' mango showed a quadratic behavior (Ferreira et al, 2020), in which the increase in doses promoted an increase in total soluble solids content up to a maximum dose of 1.3 g a.i. linear m -1 of canopy, which correspondeds to 7.64 ºBrix.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Total soluble solids content in 'Tommy Atkins' mango showed a quadratic behavior (Ferreira et al, 2020), in which the increase in doses promoted an increase in total soluble solids content up to a maximum dose of 1.3 g a.i. linear m -1 of canopy, which correspondeds to 7.64 ºBrix.…”
Section: Resultsmentioning
confidence: 98%
“…Application of paclobutrazol by irrigation system is more efficient than the conventional application; 1.4 g a.i. linear m -1 of canopy promoted a greater number of fruits and production per plant, in 'Tommy Atkins' mango (Ferreira et al, 2020). Souza et al (2018b), also evaluated 'Palmer' mango and PBZ application via drip irrigation system and reported that the dose of 1.3 g a.i.…”
Section: Resultsmentioning
confidence: 99%
“…The nutrients N and K show high mobility in the phloem and a large degree of translocation (Silva et al, 2020;Sampaio et al, 2021). As the reproductive organs have priority, these nutrients are commonly mobilized from the leaf to the fruit (Dias et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The increase in demand for high-quality mango to meet standards for local, national and international markets has resulted in the designing of new production strategies and techniques that are essential elements for its production in a fast-changing climate. For instance, the amount of rainfall in most producing regions is not adequate to meet mango water requirements, demanding the application of irrigation, biostimulants and paclobutrazol to promote flowering, fruit yield and quality [15][16][17]. Unfortunately, there are a number of bottlenecks that underpin the production of mango.…”
Section: Introductionmentioning
confidence: 99%